Role of orthodontic treatment, faculty & practitioners in influencing career choices of dental students of Faisalabad Medical University - Maria Tanveer; Hafsa Riaz; Ansar Bilal; Fatima Saeed (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: The number of orthodontic patients is increasing owing to various treatment and patient-related factors. This increased demand requires more orthodontists in the community. To determine the proportion of dental students interested in orthodontics, the significance of orthodontic-related encounters, and the contribution of orthodontic professors and practitioners as inspiration for student career decisions. METHODOLOGY: It was a cross-sectional web-based survey. 163 students from Faisalabad Medical University’s Dental Institute took part, and ethical approval was obtained. (ERC/FMU/2022-23/certificate No.48. RESULTS: The majority of students (65.6%) knew an orthodontist in their community, and 31.9% had assisted in orthodontic practice. Students who had interactions with orthodontists, orthodontic residents, and hands-on experience with orthodontics were more likely to be interested in an orthodontic career. Advancements in the field of orthodontics also significantly influenced students’ interest (p <0.001). The mean motivation level for orthodontic education was 27.0 ± 6.20, indicating good motivation among dental students. Students with the highest interest in an orthodontic career had significantly higher motivation scores (p < 0.001). CONCLUSIONS: The study highlights the importance of practical experience, exposure to the field, and innovative technologies in fostering students’ interest and motivation for a career in orthodontics.